SOCIAL ECONOMIC CHANGE AS A PRECONDITION OF ETHNIC CONFLICTS: THE CASES OF OSH CONFLICTS IN 1990 AND 2010 - K. Hyunjung (Vestnik MGIMO-Universiteta)
This article demonstrates that ethnicity itself didn’t play a significant role to cause conflicts in Osh in 1990 and 2010, but was rather a side effect or a catalyst produced inevitably by political struggle in the country. The Osh conflict in 1990 occurred at the weakening of the USSR's institutional control and decreasing material support from the center. Kyrgyzstan being the major recipient of both indirect and direct subsidies from the USSR suffered a severe economic depression because subsidies were cut or substantially reduced. Moreover, the sudden disintegration of production and trade relations further exacerbated the economic situation in Kyrgyzstan. The economic decline caused a demographic imbalance, which has contributed to increased confrontation between Kyrgyz and ethnic Uzbeks in Osh. These social tensions coincided with political mobilization under the slogans of ethnicity and contributed to the intensification of the conflict making it look similar to an ethnic conflict for an outside observer. Similarly, the Osh conflict in 2010 happened in the declining economy which was not only the result of the global economic crisis and difficulties in relations with Russia. The political short-sightedness of the Bakiyev regime in resolving problems with the air base at Manas led to complication of relations with Russia, which subsequently led to economic decline in Kyrgyzstan. The economic difficulties soon translated into institutional instability. Massive public demonstrations “framed” as an ethnic conflict by political elites intensified the battle, adding to it an “ethnic” dimension.